Effect of transcranialdirect current stimulation on the right brain temporal area on processing approach and avoidance attitudes with negation - Nuez, Aarón; Padrón, Iván; Reyes-Moreno, Cristian; Marrero, Hipólito (Frontiers in Human Neuroscience, 2022)
Language describes approach/avoidance intentionality by means of attitudinal verbs (e.g., accept vs. reject). The right superior temporal sulcus (rSTS) has been shown to be recruited in processing action goals and approach intentionality in social contexts. In this study, we examine whether transcranial direct current stimulation (tDCS) of this area improves processing of attitudinal verbs (either of approach or avoidance) in the context of affirmative and negative sentences (for example: Julio (did not)/included meat on the grocery list). After being subjected to tDCS, forty-six participants were given sentences for passive reading. Sentences were displayed in segments with a fixed time of exposition, and 1500 ms after the sentence, a verb was displayed, either the one mentioned in the sentence or an alternative one (e.g., included vs. excluded, in the example). Participants were told to read them and then press the space bar to continue the experiment. Results showed shorter latencies for approach verbs that were either mentioned in approach sentences or the alternatives in avoidance sentences, both in affirmative and negative versions under anodal conditions compared to sham conditions. Thus, anodal stimulation of rSTS affected accessibility of approach verbs that was not modulated either by being mentioned or by sentence polarity. In addition, mentioned verbs had shorter reading times than the alternative ones in negative sentences in anodal vs. sham condition. This suggests stimulation caused an effect of negation in activation of the mentioned verb. Implications are discussed in the context of the role of the rSTS in processing attitudinal verbs and negation to understand better approach and avoidance mediated by language in the framework of the two-step model of negation processing.